The Möbius strip of memory and history, faith, and fascism : in an Italian Prisoner of War memoir - Houston, Peter (Stellenbosch Theological Journal, 2023)
Giovanni Palermo was an Italian prisoner of war captured at the battle of Bardia on 3 January 1941 in Libya. He was transferred by ship to Durban and from there, taken to Zonderwater prisoner of war (POW) camp near Pretoria. Palermo published his memoir in 1972 detailing his capture and POW experiences. A close reading of his translated memoir presents several historical challenges. He uncritically makes his personal bias plain from the start, yet at the same time sees himself as the custodian of the true narrative of Italian POW history, even where the historical record indicates a contrary truth to his. Religious and political ideologies present themselves like a Möbius strip at various points throughout his memoir, not least with an opening endorsement by a Christian religious figure who frames what is to follow. Palermo's strongly held views on purity, his self-belief that he is the bearer of the real truth, and his desire to make Italy great again have contemporary societal and theological resonances.